Unraveling the Depths: Exploring Maritime Terrorism through International and National Legal Perspectives - Prasista Maolana; Satria Unggul Wicaksana Prakasa (Universitas Internasional Batam, 2023)
Acts of terror are extraordinary crimes with very complicated impacts, where the perpetrators commit acts of violence and threaten targets that are determined randomly based on certain categories. The various terrorist incidents that have occurred in Indonesia do not rule out the possibility of similar incidents being even more horrific and resulting in more victims in the future. Indonesia as an archipelagic country views maritime security as an important aspect of maritime domain governance. The Sulu-Sulawesi sea area is a vulnerable route throughout Asia, it is considered that crimes committed in the Sulu Sea are extreme crimes called maritime terrorism which can threaten the sovereignty of a country. Terrorism has become an increasingly serious concern in Indonesia since the Bali Bombing and other terrorist tragedies. From these problems, the formulation of the problems that must be answered in this study is (1) What are the legal remedies for perpetrators of maritime terrorism in the perspective of international law, 2) How are efforts to enforce violations of state sovereignty in the national maritime area in maintaining national defense. This study uses the normative legal research to analyze from a legal perspective regarding maritime terrorism by terrorists that endanger state sovereignty, and the national sea in maintaining national defense.